2017
DOI: 10.1111/mec.14333
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of adaptive responses to ocean acidification

Abstract: Some populations of marine organisms appear to have inherent tolerance or the capacity for acclimation to stressful environmental conditions, including those associated with climate change. Sydney rock oysters from the B2 breeding line exhibit resilience to ocean acidification (OA) at the physiological level. To understand the molecular basis of this physiological resilience, we analysed the gill transcriptome of B2 oysters that had been exposed to near-future projected ocean pH over two consecutive generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 80 publications
0
35
0
Order By: Relevance
“…() recently showed that the greater responsiveness of selectively bred Sydney rock oysters to OA is due to their better capacity to compensate for CO 2 ‐induced extracellular acid‐base disturbances, by eliminating metabolic CO 2 through higher and more energy efficient filtration rates. Differential responses to CO 2 stress between populations of Sydney rock oysters have also been previously investigated at the protein and transcriptional levels (Goncalves et al., , ; Thompson et al., ). Proteomic analysis revealed that the majority of the differentially regulated proteins were found at lower concentrations in the gills of selectively bred oysters under CO 2 stress relative to ambient conditions, suggesting potential cellular injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…() recently showed that the greater responsiveness of selectively bred Sydney rock oysters to OA is due to their better capacity to compensate for CO 2 ‐induced extracellular acid‐base disturbances, by eliminating metabolic CO 2 through higher and more energy efficient filtration rates. Differential responses to CO 2 stress between populations of Sydney rock oysters have also been previously investigated at the protein and transcriptional levels (Goncalves et al., , ; Thompson et al., ). Proteomic analysis revealed that the majority of the differentially regulated proteins were found at lower concentrations in the gills of selectively bred oysters under CO 2 stress relative to ambient conditions, suggesting potential cellular injury.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, wild type oysters exhibited an up‐regulation of their differential proteins in response to elevated CO 2 (Thompson et al., ). At the level of gene expression, transgenerational exposure to elevated CO 2 (three consecutive generations) resulted in the differential regulation of genes associated with antioxidant defence, metabolism and the cytoskeleton in selectively bred oysters, while less pronounced changes in transcript levels were observed in wild type oysters (Goncalves et al., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sydney rock oyster, Saccostrea glomerata, has experienced decades of artificial selection for growth and disease resistance, which interestingly also corresponds to resilience against low pH [105,128,129]. This resilient family of oysters shows increases in resting metabolic rates [105] and in genes associated with the CSR and immune system, such as HSPs, antioxidant enzymes glutathione Stransferases and C1q domain proteins under ambient conditions [55,56]. These enzymes are then downregulated under transgenerational moderate pCO 2 (625 μatm) when compared to a control family [55,56].…”
Section: Observation 3: High Pco 2 Exposure Often Induces the Cellulamentioning
confidence: 99%
“…Transcriptomic studies have proven to be a powerful approach for identifying genes and understanding pathways that shape organismal response to OA, and have been used to help elucidate potential trade-offs that result from acclimatization (Evans and Hofmann, 2012) , including genes associated with biomineralization, acid-base regulation, and metabolic function (Evans et al, 2013;Davies et al, 2016;Li et al, 2016;Goncalves et al, 2017;Wong et al, 2018;Griffiths et al, 2019) . From this literature it has been hypothesized that there is a trade-off between maintaining calcification versus other core functions (Wood et al, 2008) , whereby increased or sustained calcification under continued exposure may become too costly over time.…”
Section: Introductionmentioning
confidence: 99%